Therapeutic effects of myrrh extract and myrrh-based silver nanoparticles on Trichinella spiralis-infected mice: parasitological, histopathological, and immunological (IFN-γ, IL-10, and MMP-9) investigations - Abd-ELrahman, Salwa Mahmoud; Dyab, Ahmed Kamal; Mahmoud, Abeer El-sayed; Mohamed, Shaymaa M.; Fouad, Alamira Marzouk; Gareh, Ahmed; Asseri, Jamal; Dahran, Naief; Alzaylaee, Hind; Albisihi, Hayat M.; Abd Elrahman, Ahmed Mahmoud; Alsharif, Fahd M.; et al. (Frontiers in Veterinary Science, 2024)
IntroductionTrichinellosis, caused by Trichinella spiralis (T. spiralis), remains a prevalent parasitic zoonosis. Developing new drugs targeting and understanding the immune response against the infection is imperative. Previous research has inadequately explored the efficacy of crude myrrh extract and myrrh-based silver nanoparticles (AgNPs) against trichinellosis, as well as their impact on histopathological, and immunological factors.MethodsThis study evaluated the effects of silver nanoparticles biosynthesized using myrrh, crude myrrh extracts, and albendazole on the intestinal phase of T. spiralis. It also examined the associated histopathological changes and alterations in key immunological markers, including Interferon-gamma (IFN-γ), Interleukin-10 (IL-10), and Matrix Metalloproteinase-9 (MMP-9). Five groups of 12 mice were allocated as follows: group 1: non-infected, non-treated (negative control), group 2: infected, non-treated (positive control), group 3: infected and treated with biosynthesized silver nanoparticles (40 μg/mL), group 4: infected and treated with myrrh crude extract (800 mg/kg), and group 5: infected and treated with albendazole (50 mg/kg). Treatment was orally administered starting on the 2nd day post-infection and continued for three successive days. Mice of all groups were euthanized on the 6th day post-infection, and the intestine of each was isolated for parasitological, histopathological, and immunohistochemistry evaluation of MMP-9, as well as assessment of cytokines level (IFN-γ and IL-10 gene expressions) via Real-time PCR technique.ResultsThe present study showed a considerable reduction in adult worm count among the treated groups. The mortality rates of adult worms were 88.64% in the silver nanoparticles treated group, 85.17% in the myrrh crude extract group, and 94.07% in the albendazole-treated group. Histopathological examination revealed prominent alterations in the intestine of the infected non-treated mice, which were markedly restored by treatment. Immunohistochemical examination accompanied by significant reduction in MMP-9 expression in the infected mice treated with AgNPs compared to the infected non-treated group, reflecting the role of AgNPs in downgrading the inflammatory reaction in the intestine of infected mice.ConclusionCollectively, this study demonstrates the novel antiparasitic potential of silver nanoparticles biosynthesized with myrrh against T. spiralis in infected mice. The treatment was associated with moderate rise in IFN-γ gene expression and IL-10 expression, highlighting its therapeutic efficacy against T. spiralis.